The Role of the Head of Early Childhood Education (PAUD) as an Administrative and Managerial Leader in Realizing a Quality Institution - Qurratu’ain, Nisrina; Syarafina, Nissa Azzahra; Jamal, Alya Rizqiyah; Perwitasari, Nur Aini; Suhardi, Suhardi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to examine the role of the Head of PAUD as an administrative and managerial leader in realizing a quality early childhood education institution. The research uses the library study method by reviewing various sources of academic literature. The results of the study show that the Head of PAUD has strategic responsibilities in the aspects of planning, organizing, implementation, supervision, and efficient management of institutional resources. The Head of PAUD's administrative role encompasses the management of administration, reports, and budget, while the managerial role relates to the application of the POAC management principles (Planning, Organizing, Actuating, Controlling). Leadership styles such as visionary, transformational, and charismatic are proven to have a significant impact on improving the quality of teaching, the professionalism of educators, and a conducive learning atmosphere. The conclusion of this research affirms that the effective and professional leadership of the Head of PAUD is the main factor in creating a superior institution that is responsive to the development of the times.